Ordered Data Analysis, Modeling and Health Research Methods In Honor of H. N. Nagaraja's 60th Birthday - Choudhary, Pankaj; Nagaraja, Chaitra H.; Ng, Hon Keung Tony (Springer Proceedings in Mathematics & Statistics, 2015)
This volume presents an eclectic mix of original research articles in areas covering the analysis of ordered data, stochastic modeling and biostatistics. These areas were featured in a conference held at the University of Texas at Dallas from March 7 to 9, 2014 in honor of Professor H. N. Nagaraja's 60th birthday and his distinguished contributions to statistics. The articles were written by leading experts who were invited to contribute to the volume from among the conference participants. The volume is intended for all researchers with an interest in order statistics, distribution theory, analysis of censored data, stochastic modeling, time series analysis, and statistical methods for the health sciences, including statistical genetics.